A Japanese Moral Education: A Role Model for Virtuous Life - Kahraman, Cahit (Border Crossing, 2018)
“Good-hearted person” is referred to a personality with good morals, who is fair, decent and neat. In order to raise a good hearted person, or for a person to have good virtues, it is necessary to mention the significance or sublimity of these values. When asked how is raised a person with morals in Japan, İnazo Nitobe stated that what teaches these values are Bushido warrior codes. With Confucianism prevailing in Edo period (1603-1868), Shushin education taught how to do good deed. Confucius’ work “Daigaku” specifies four main factors for the ruling of the country: These can be explained as “Shushin” (self-nurturing), “Seika” (family nurturing), “Chikoku” (protecting the homeland) and “Heitenka” (endless respect for the Emperor). Prior to the World War II many values of good morals have been a part of Shushin education and since the first grade of the primary school was taught how to become a good Japanese. In 1945, Shushin education was ceased by the Allied Forces. In the 1960’s, considering that they lost Japaneseness and Japanese soul in their character, the Japanese made three month Seishin (spirituality) education mandatory for every employee. In the present day Japan, Dōtoku (Moral Knowledge Course) is provided from the primary to high school. As work life starts this education continues with Kyöyö (Workplace Training) journals. This study is an analysis of Dōtoku coursebooks and some workplace journals.